Offshoring and firm innovation: The moderating role of top management team attributes - Mihalache, Oli R.; Jansen, Justin J. J. P.; Van Den Bosch, Frans A. J.; Volberda, Henk W. (Strategic Management Journal, 2012)
Abstract This study attempts to increase the understanding of how offshoring influences the introduction of new products and services. Focusing on the offshoring of those business functions that provide direct knowledge inputs for innovation (i.e., production, R&D, and engineering), we propose that offshoring has an inverted U‐shaped influence on firm innovativeness. Additionally, we provide an upper echelon contingency perspective by considering the moderating role of two top management team (TMT) attributes (i.e., informational diversity and shared vision). Using a cross‐industry sample with lagged data, we find that offshoring has an inverted U‐shaped influence on firm innovativeness and that this relationship is steeper in firms with high TMT informational diversity and in firms with low TMT shared vision. Copyright © 2012 John Wiley & Sons, Ltd.